Study On The Development Of A Waterfront City Concept Based On Sustainable Tourism In The Alue Naga Coastal Area, Banda Aceh City - Agung Pranawa Maheswara; Muhammad Ilham (LPPM Universitas PGRI Sumatera Barat, 2024)
The development of coastal areas, especially in Banda Aceh City, has a great potential to provide significant economic, social, and environmental benefits. The main focus is on Alue Naga Village, which has unique characteristics with two waterfronts, namely the sea and the river. This potential can be developed through the concept of waterfront city where this development is carried out from an internal perspective in the form of fishing dock facilities, structuring coastal settlements, and creating recreational areas in the form of parks. Meanwhile, external potentials, such as being closed to the access point to the toll road and the proximity of the Aceh industrial area can also support the development of this area. This research aims to examine the development of the waterfront city area in Alue Naga Village with a focus on the concept of sustainable tourism and environmental sustainability. The results of this research include design and analysis based on the characteristics and potential of the area integrated in the design. It is expected that this research can provide valuable insights for stakeholders, particularly the government to plan and develop this area, with significant positive impacts for the community and the environment